HyperCell: A Bio-inspired Design Framework for Real-time Interactive Architectures - Chang, Jia-Rey (A+BE | Architecture and the Built Environment, 2018)
This pioneering research focuses on Biomimetic Interactive Architecture using “Computation”, “Embodiment”, and “Biology” to generate an intimate embodied convergence to propose a novel rule-based design framework for creating organic architectures composed of swarm-based intelligent components. Furthermore, the research boldly claims that Interactive Architecture should emerge as the next truly Organic Architecture. As the world and society are dynamically changing, especially in this digital era, the research dares to challenge the Utilitas, Firmitas, and Venustas of the traditional architectural Weltanschauung, and rejects them by adopting the novel notion that architecture should be dynamic, fluid, and interactive. This project reflects a trajectory from the 1960’s with the advent of the avant-garde architectural design group, Archigram, and its numerous intriguing and pioneering visionary projects. Archigram’s non-standard, mobile, and interactive projects profoundly influenced a new generation of architects to explore the connection between technology and their architectural projects. This research continues this trend of exploring novel design thinking and the framework of Interactive Architecture by discovering the interrelationship amongst three major topics: “Computation”, “Embodiment”, and “Biology”. The project aims to elucidate pioneering research combining these three topics in one discourse: “Bio-inspired digital architectural design”. These three major topics will be introduced in this Summary. “Computation”, is any type of calculation that includes both arithmetical and nonarithmetical steps and follows a well-defined model understood and described as, for example, an algorithm. But, in this research, refers to the use of data storage, parametric design application, and physical computing for developing informed architectural designs. “Form” has always been the most critical focus in architectural design, and this focus has also been a major driver behind the application computational design in Architecture. Nonetheless, this research will interpret the term “Form” in architecture as a continual “information processor” rather than the result of information processing. In other words, “Form” should not be perceived only as an expressive appearance based computational outcome but rather as a real-time process of information processing, akin to organic “Formation”. Architecture embodying kinetic ability for adjusting or changing its shape with the ability to process the surroundings and feedback in accordance with its free will with an inherent interactive intelligent movement of a living body. Additionally, it is also crucial to address the question of whether computational technologies are being properly harnessed, if they are only used for form-generating purposes in architecture design, or should this be replaced with real-time information communication and control systems to produce interactive architectures, with embodied computation abilities? “Embodiment” in the context of this research is embedded in Umberto Eco’s vision on Semiotics, theories underlying media studies in Marshall McLuhan’s “Body Extension” (McLuhan, 1964), the contemporary philosophical thought of “Body Without Organs” (Gilles Deleuze and Félix Guattari, 1983), the computational Logic of ‘Swarm Behavior’ and the philosophical notion of “Monadology” proposed by Gottfried Leibniz (Leibniz, 1714). Embodied computation and design are predominant today within the wearable computing and smart living domains, which combine Virtual and Real worlds. Technical progress and prowess in VR development also contribute to advancing 3D smart architectural design and display solutions. The proposed ‘Organic body-like architectural spaces’ emphasize upon the realization of a body-like interactive space. Developing Interactive Architecture will imply eliciting the collective intelligence prevalent in nature and the virtual world of Big Data. Interactive Architecture shall thus embody integrated Information exchange protocols and decision-making systems in order to possess organic body-like qualities. “Biology”, in this research explores biomimetic principles intended to create purposedriven kinetic and organic architecture. This involves a detailed study/critique of organic architecture, generating organic shapes, performance optimization based digital fabrication techniques and kinetic systems. A holistic bio-inspired architecture embodies multiple performance criteria akin to natural systems, which integrate structural, infrastructure performances throughout the growth of an organic body. Such a natural morphogenesis process of architectural design explores what Janine M. Benyus described as “learning the natural process”. Profoundly influenced by the processes behind morphogenesis, the research further explores Evolutionary Development Biology (Evo-Devo) explaining how embryological regulation strongly affect the resulting formations. Evo-Devo in interactive architecture implies the development of architecture based on three fundamental principles: “Simple to Complex”, “Geometric Information Distribution”, and “On/Off Switch and Trigger.” The research seeks to create a relatively intelligent architectural body, and the tactile interactive spatial environment by applying the extracted knowledge from the study of the aforementioned principles of Evo-Devo in the following fashion: A. Extract a Self-Similar Componential System based approach from the “Simple to Complex” principle of Evo-Devo B. Extract the idea of “Collective Intelligence” from “Geometric information Distribution” principle of Evo-Devo C. Extract the principle of “Assembly Regulation” from “On/Off switch and trigger” principle of Evo-Devo The “HyperCell” research, through an elaborate investigation on the three aforementioned topics, develops a design framework for developing real-time adaptive spatial systems. HyperCell does this, by developing a system of transformable cubic elements which can self-organize, adapt and interact in real-time. These Hypercells shall comprise an organic space which can adjust itself in relation to our human bodies. The furniture system is literally reified and embodied to develop an intra-active space that proactively provokes human movement. The space thus acquires an emotive dimension and can become your pet, partner, or even friend, and might also involve multiple usabilities of the same space. The research and its progression were also had actively connected with a 5-year collaborative European Culture project: “MetaBody”. The research thus involves exploration of Interactive Architecture from the following perspectives: architectural design, digital architectural history trajectory, computational technology, philosophical discourse related to the embodiment, media and digital culture, current VR and body-related technology, and Evolutionary Developmental Biology. “HyperCell” will encourage young architects to pursue interdisciplinary design initiatives via the fusion of computational design, embodiment, and biology for developing bio-inspired organic architectures.